Penggunaan Game Theory dalam Ilmu Sosial - Situmorang, James R. (Business Administration Study Program - Universitas Katolik Parahyangan, 2015)
Game theory has actually been initiated by several mathematicians but game theory began to receive widespread attention since the publication of a book entitled Theory of Games and Economic Behavior, in 1944, which was written by a mathematician John von Neumann and economists Oskar Morgenstern. Game theory continues to evolve to this day and although it is still considered as part of economics but game theory had been applied in various disciplines such as psychology, politics, management, social sciences. So that people can understand it more easily, can be used examples of simple games, among others, two-person zero-sum game, maximin and minimax, ultimate game, linear programming. The game is simple to be useful because most of the game invites players to use logic to achieve profits for himself. Keywords: game theory, mathematics, payoff, matrix, saddle point